When the Unspoken Speaks: As Seen in Andriani Marshanda’s You Used Me and Letter to God - Akun, Akun (Bina Nusantara University, 2018)
Repressed unresolved psychological conflicts for some people can be safely channeled into a poetical literary work as—despite its short and audio-visually framed and limited form— it could speak of bigger ideas with more freedom, and English as a medium had its own capacity to truthfully communicate the ideas. The goal of this study was to reveal the spoken and the unspoken truths behind Andriani Marshanda’s poetic expressions and their visualization in The Unspoken 1: You Used Me and The Unspoken 2: Letter to God. This research focused on how English played an important role in safely channeling the ideas and how oxymoronic metaphors used in the poems speak more of the unspoken words and worlds within the poems. It used library research by employing a textual analysis of the selected poems using Macherey’s concept of the spoken and unspoken. The additional data were also taken from the real life of the author found in printed and electronic media. The analysis will be focused on the revelation of the silence or unspoken that unconsciously infiltrates the spoken or expressed lines of the poems. It is concluded that the poems speak more bluntly of the persona’s lack of freedom, feelings of being exploited, incongruous and dilemmatic state of mentality, and a newly perceived, happily anticipated, and more truly liberated life.